CLINICAL STUDY of NATURAL INFECTION BY Trypanosoma cruzi IN DOGS RESIDING IN A RURAL AREA IN MATO GROSSO do SUL STATE, BRAZIL - Souza, A. I. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2008)
This study was carried out to describe the clinical characteristics of natural infection caused by Trypanosoma cruzi in dogs that reside in a rural area of Mato Grosso do Sul State, Brazil. Conventional and nonconventional diagnostic methods were used for screening T. cruzi infection in 75 dogs that lived in the area. Cardiovascular tests and biochemical examination of sera were also performed in four confirmed positive dogs. The following techniques were employed: indirect immunofluorescence test (IFAT), enzyme-linked immunosorbent assay with T. cruzi epimastigote antigens (EAE-ELISA) and enzyme-linked immunosorbent assay with T. cruzi excreted-secreted trypomastigote antigens (TESA-ELISA) with antibodies detected in 45.33% (n = 34), 24.0% (n = 18) and 12.0% (n = 9) of the dogs, respectively. The current prevalence of the infection was confirmed as 10.7% (n = 8) by immunoblotting test with T. cruzi excreted-secreted antigens (TESA-blot). The test that showed the best concordance index (Kappa; 0.93), sensitivity (100%) and specificity (98.5%) was TESA-ELISA, that when associated with IFAT had the same results as those obtained by TESA-blot (10.7%). Three out of the four chagasic animals showed enlarged cardiac silhouette on X-ray and an increase of the P-wave duration and QRS complex in electrocardiogram. Two dogs presented conduction disturbances, right bundle branch block in one dog and first-degree atrioventricular block and sinus arrest in another. The ecodopplercardiography presented left-ventricular-wall thickness increased during diastole, decrease of the shortening fraction and inversion in the speed peaks of the E and A waves, indicating the presence of systolic and diastolic disorders. The four animals showed enzymatic activities of creatine kinase (221-404 U/L), MB fraction of creatine kinase (189-304 U/L), elevated total proteins (7.6-10.2 g/dL) and total globulins (4.6-7.7g/dL) and reduction of albumin/globulin ratio, which suggested a myocardial injury and continuous antigenic stimulus.
Keywords: Chagas' disease; myocarditis; TESA-blot; TESA-ELISA Trypanosoma cruzi